Deferred statistical convergence of order ? in topological groups - Sengul, Hacer; Et, Mikail; Cakalli, Huseyin (Amer Inst Physics, 2019)
In this paper, the concept of deferred statistical convergence of order a is generalized to topological groups, and some inclusion relations between the set of all statistically convergent sequences of order a in topological groups and the set of all deferred statistically convergent sequences of order a in topological groups are given.
3rd International Conference of Mathematical Sciences (ICMS) -- SEP 04-08, 2019 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis